Neural Correlates of Musical Creativity: Differences between High and Low Creative Subjects - Villarreal, M.F. (2013)
Previous studies of musical creativity suggest that this process involves multi-regional intra and interhemispheric interactions, particularly in the prefrontal cortex. However, the activity of the prefrontal cortex and that of the parieto-temporal regions, seems to depend on the domains of creativity that are evaluated and the task that is performed. In the field of music, only few studies have investigated the brain process of a creative task and none of them have investigated the effect of the level of creativity on the recruit networks. In this work we used magnetic resonance imaging to explore these issues by comparing the brain activities of subjects with higher creative abilities to those with lesser abilities, while the subjects improvised on different rhythmic fragments. We evaluated the products the subjects created during the fMRI scan using two musical parameters: fluidity and flexibility, and classified the subjects according to their punctuation. We examined the relation between brain activity and creativity level. Subjects with higher abilities generated their own creations based on modifications of the original rhythm with little adhesion to it. They showed activation in prefrontal regions of both hemispheres and the right insula. Subjects with lower abilities made only partial changes to the original musical patterns. In these subjects, activation was only observed in left unimodal areas. We demonstrated that the activations of prefrontal and paralimbic areas, such as the insula, are related to creativity level, which is related to a widespread integration of networks that are mainly associated with cognitive, motivational and emotional processes. © 2013 Villarreal et al.